Contextualization of UN human rights indicators: Modifying "right to work" indicators for application in Taiwan. Issue 3 (27th May 2018) - Huang, Yibee; Chen, Chun-Hung; Chen, Chung-Ning; Huang, Mab; Huang, Song-Lih
ABSTRACT: Human rights indicators are tools for monitoring a government's progress in fulfilling its human right obligations. In 2012, the United Nations released a manual of human rights indicators that includes a conceptual framework and illustrative indicators. This article reports on an examination of "right to work" indicators appropriate for use in Taiwan. The review was undertaken under the auspices of the executive branch of the government of Taiwan in consultation with panels of experts, officials of statistical departments, and persons from vulnerable groups, to contextualize the indicators for future implementation. The authors modified several indicators suggested in the manual and created one additional attribute on collective labor rights. Following an analysis of the indicators, the article highlights several issues that require further attention, including the feasibility of disaggregating administrative data, the use of indicators at subnational levels of governments, and the development of human rights indicators for particular groups.